Alterations of Total Serum Immunoglobulin Concentrations in Pemphigus and Pemphigoid: Selected IgG2 Deficiency in Bullous Pemphigoid - Khil'chenko, Stanislav; Boch, Katharina; van Beek, Nina; Vorobyev, Artem; Zillikens, Detlef; Schmidt, Enno; Ludwig, Ralf J. (Frontiers in Medicine, 2020)
Pemphigus and pemphigoid diseases are organ-specific autoimmune diseases of the skin and/or mucous membranes, which are caused by autoantibodies targeting structural proteins of the skin. In other autoimmune diseases, a high prevalence of primary antibody deficiencies was noted. Conversely, a high prevalence of autoimmune diseases is reported in patients with primary antibody deficiencies. With the exception of one study, pointing towards a decrease of IgG in pemphigus patients, with a relative enrichment of IgG4, serum immunoglobulin (Ig) concentrations had not been studied in pemphigus and pemphigoid. Hence, we here aimed to investigate serum concentrations of IgM, IgA, IgG, and IgG1-4 in pemphigus and pemphigoid patients, as well as in healthy controls. Serum Ig concentrations were determined by ELISA in 105 healthy controls, 100 pemphigus vulgaris (PV), 100 pemphigus foliaceus (PF), 99 bullous pemphigoid (BP) and 55 linear IgA bullous dermatosis (LAD) patients. In healthy controls, age had a significant impact on Ig serum concentrations: In controls at ages of 69 years or older, IgM and IgG were decreased, while all other Ig, except IgA and IgG4, were increased. When stratified by sex, lower IgM concentrations were observed in males. When corrected for age and/or sex, and compared to controls, an increase of serum IgA was noted in LAD. In almost all patient cohorts, an increase of IgG1 and IgG4 was observed, while a decrease in IgG2 or IgG3 was seen in BP or PV patients. This points towards a possible association of BP with IgG2 deficiency, and warrants evaluation of IgG2 in BP patients prior to immunosuppressive therapy.